Development of 3D Animation Media on Computational Thinking Skills Integrated with PISA Using a Deep Learning Approach - Siti Khaulah; Novianti; T Rafli Abdillah (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study was to develop 3D animated video learning media for computational thinking skills integrated with PISA questions and to determine the feasibility and practicality of the learning media using the Plotagon application with the discussion of PISA questions. The research design used the 4D development model with ADDIE development, namely: analysis, design, development, and evaluation. The research instruments used were media and material expert assessments, practitioners, and student questionnaires. The results of the media validation development obtained a percentage of 93.25% with a very valid category. Material expert validation obtained a percentage of 91.45% with a very valid category. Practitioner validation obtained a percentage of 90.38% with a very practical category. Meanwhile, the results of the small group trial obtained a percentage of 85%, while the large group trial obtained a percentage of 83%. Therefore, the results of the 3D animated video media development research are very feasible and practical to be used and implemented in the learning process with a deep learning approach to computational thinking skills.